A fronteira como lugar das diferenças : Rikbaktsa entre a Igreja e o Estado (1930 - 1985) - Santos, Julio César dos (2018)
The frontier as a place of differences: Rikbaktsa between church and the State is a narrative built from the tools of social history, using the Research Center Father João Bosco Bournier and the extinct Development Company of Mato Grosso - CODEMAT - files and also the methodological resources of oral history. The text analyzes the reoccupation process northwest of Mato Grosso between 1930 and 1985 as it chronicles the social processes arising from the meeting of Jesuit missionaries, rubber tappers and settlers with Indigenous Rikbkatsa in particular inhabitants of Erikbaktsa territory located on the banks of the river Juruena and river of Sangue, in the northwest of Mato Grosso. The differences between these subjects and the ways territorial frontier and ethnicity are reconfigured is the central aspect investigated in the course of the research. The main references of the text are: José de Souza Martins, through which the frontier is thought as a space of inhumanities; Tevzan Todorov, who bases the process of disqualification of the different as a justification for the practices of violence and expropriation; Fredrik Barth contributes to the idea of violation of ethnicity borders; territoriality and temporality, they have as reference Rogério Haesbart, Milton Santos and Reinhart Koselleck. From the association of the thought of these authors with the complexity of the relations between the subjects analyzed with support in those sources, the central idea emerged that is precisely the frontier and the territory being thought from the dynamics imposed by the encounter between indigenous people, religious, rubber tappers and settlers.